Individual Perceptions of Institutional Uncertainty: Evidence from India - Rose, Elizabeth L.; Lahiri, Nandini (Journal of Comparative International Management, 2022)
The nature of a location’s institutional environment affects businesses and individual citizens, and the extent to which people trust institutions may affect regulatory compliance. We investigate institutional trust among three groups in India: founders of entrepreneurial ventures, second (or later) generation managers of family firms, and salaried employees. Rather than treating the institutional environment as monolithic, we consider six components that represent policy, implementation, and security: central and state governments, bureaucracy, judiciary, army, and police. Based on large-scale, questionnaire-based data, we find evidence that the antecedents of trust differ across both the three groups of respondents and the six aspects of the institutional environment. Institutional environment, entrepreneurs, family firms, India, emerging markets, trust, optimism, uncertainty